The Relationship Between Product Quality and Purchase Intention at PT. Lontar Papyrus Pulp and Paper Medan: Hubungan Kualitas Produk dengan Minat Beli Pada PT. Lontar Papyrus Pulp and Paper Medan - Mega Sanjaya; Darwan Tanady; Jung Sen (Jurnal Kolaboratif Sains, 2023)
customer's expectations. It is the group of features and characteristics of a saleable good which determine its desirability and which can be controlled by a manufacturer to meet certain basic requirements. Research is conducted at PT. Lontar Papyrus Pulp and Paper Medan which having problem with the customers’ purchase intention because of the product quality of the company. The indicators of variable X (Product quality) are performance, features, conformance, reliability, durability, serviceability, aesthetics, and customer perceived quality. The indicators of variable Y (Customer Purchase Intention) are product orders, customer satisfaction, loyalty, and repeat order. The population that the writer uses is the customers of PT. Lontar Papyrus Pulp and Paper Medan which are 92 people. To determine sample size, use simple random technique which all population member has same chance to be selected as sample. The results of the data calculations are product quality has relationship with purchase intention which can be seen from hypothesis test and has a positive and significantly strong relationship with purchase intention from correlation test and linear regression equation. The writer give several recommendations which make sure they sell all products in a good and complete condition to customers, check the products so that they can do all the features for its intended purpose, provide a clear and trusted warranty for certain period of time to customers, and may regularly to do product quality check up on the products they offering to the customers.